Perlindungan Hukum Bagi Peserta Bpjs Kesehatan Atas Penolakan Pelayanan Kesehatan Virus Corona Di Rumah Sakit - Ahmad Teguh Faruq Saputra; AM. Hasan Ali; Ahmad Chaerul Hadi (JOURNAL of LEGAL RESEARCH, 2022)
In this thesis, the main issue is how to protect people who use the BPJS Kesehatan health insurance plan. The government's role and the hospital's responsibility for not providing coronavirus health care in hospitals are also important. For this study, the goal is for researchers to find out what kind of legal protection BPJS Health participants have. They also want to find out what the government's role and accountability are for people who don't use coronavirus health care in hospitals. This type of qualitative research is based on an empirical normative approach, which means that it looks at laws and regulations, books, and journal articles (library research), as well as the results of interviews with people who work for related agencies. Then, it describes and connects these laws and regulations to the research. Legal protection for BPJS Kesehatan participants who don't want to use coronavirus health services in hospitals is one thing this study will help you learn about. The government and hospitals also play a role.